Cerebral palsy and multiple births. Issue 3 (November 1996) - Pharoah, P O; Cooke, T
Abstract : AIM: To compare the birthweight specific prevalence of cerebral palsy in singleton and multiple births. METHODS: Registered births of babies with cerebral palsy born to mothers resident in the counties of Merseyside and Cheshire during the period 1982 to 1989 were ascertained. RESULTS: The crude prevalence of cerebral palsy was 2.3 per 1000 infant survivors in singletons, 12.6 in twins, and 44.8 in triplets. The prevalence of cerebral palsy rose with decreasing birthweight. The birthweight specific prevalence among those of low birthweight < 2500 g was not significantly different in singleton than in multiple births. Among infants weighing > or = 2500 g, there was a significantly higher risk in multiple than in singleton births. The higher crude cerebral palsy prevalence in multiple births is partly due to the lower birthweight distribution and partly due to the higher risk among normal birthweight infants. CONCLUSIONS: Multiple birth babies are at increased risk of cerebral palsy. There is also an increased risk of cerebral palsy within a twin pregnancy if the co-twin has died in utero.